Parental Monitoring Moderates the Relation Between Radio Exposure and Adolescent Alcohol and Tobacco Use: Preliminary Findings From a National Survey. Issue 4 (4th July 2017) - Smith, Lia J.; Aycock, Chase; Hook, Kimberly; Chen, Pan; Rueger, Sandra Yu
ABSTRACT: Media exposure is a risk factor and parental monitoring is a protective factor against adolescent alcohol and tobacco use. Music-related media, however, are underexplored. The National Survey of Parents and Youth was utilized to examine music-related media as a risk factor and parental monitoring as a protective factor for alcohol and cigarette use. Multilevel modeling demonstrated that music exposure was related to higher levels and parental monitoring was related to lower levels of substance use. Parental monitoring attenuated the effect of radio exposure on alcohol and cigarette use. Further investigation of music, parental monitoring, and adolescent substance use is needed.